PkM Pendampingan UD. Sido Mulyo Untuk Penguatan Ekonomi Di Masa Pandemi Covid-19 - Novita Fitriani; Lia Nurfiana; Iffa Anindyawati; R Hadapaningradja Kusumodestoni; Sarwido; Sisno Riyoko; Azzah Nor Laila; Gun Sudiryanto; Dias Prihatmoko (Universitas Islam Nahdlatul Ulama Jepara, 2022)
UD chips business. Sido Mulyo is a chip business that has grown rapidly so that it can improve the economy of partners. UD. Sido Mulyo is one of the big chip agents in the Batealit sub-district. UD. Sido Mulyo produces various types of chips, which are distributed to consumers in various sizes and prices. The implementation method used by the KKN team in partnering with UD. Sido Mulyo, namely socialization, training, mentoring and evaluation. UD. Sido Mulyo provides an opportunity for people whose age is no longer productive to join their company, so that these people still get income to support their economy during this pandemic